Cooperative Networked Quadrotor UAV Formation and Prescribed Time Tracking Control with Speed and Input Saturation Constraints - Zhikai Wang; Yifan Qin; Fazhan Tao; Zihao Wu; Song Gao (Drones, 2025)
This paper addresses the challenges of cooperative formation control and prescribed-time tracking for networked quadrotor UAVs under speed and input saturation constraints. A hierarchical control framework including position formation layer and attitude tracking layer is proposed, which achieves full drive control of an underactuated UAV formation system by introducing the expected tracking Euler angle. For the outer-loop position control, a distributed consensus protocol with restricted state and control inputs is designed to ensure formation stability with customizable spacing and bounded velocity. The inner-loop attitude control employs a prescribed-time sliding mode attitude controller (PTSMAC) integrated with a prescribed-time extended state observer (PTESO), enabling rapid convergence within user-defined time and compensating for unmodeled dynamics, wind disturbances, and actuator saturation. The effectiveness of the proposed algorithm was demonstrated through Lyapunov stability. Comparative simulations show that the proposed method has significant advantages in high-precision formation control, convergence time, and input saturation.